Narrativas audiovisuais nas redes sociais: o consumo como elemento de identidade na campanha da Panvel - Mantello, Paulo Francisco [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In order to answer the demands of users of the new digital media, experimentations have been made in the media communication field. Adversitising has significantly contributed in this quest using audiovisual narratives and storytelling resource. This paper investigates the use of narrative in audiovisual products whose intent is to convey brand content. This research has as object two films of an advertising campaign from Panvel Pharmacies, hosted on Youtube and shared by the enterprise principally on Facebook: audiovisual The History of Lilinho (2011) and The History of Sofia (2012). The research analyzes how the narrative seeks to involve the consumer emotionally to establish a bond with the brand from the psychological emptiness of human being. It is understood that there is a search for identity that stories solidify momentarily in a kind of advertising denial. Social networking sites appear to enhance this search with the possibility of interaction and production of what is consumed. One way to explore the power of narrative has been the adaptation of atistic and literacy works to attract and engage consumers. The analysis was promoted by narrative study from the intersection of Communication and Psychology. Salmon and Nuñez were used to the case study to deal with storytelling; Kotler for marketing and advertising; Lévy and Recuero to new technologies and media; and Baudrillard and Bauman to society and consumption. In the fields of audiovisual and adaptation Aumont and Bulhões were adopted, also Jullier and Marie to assist in film analysis. It sought further knowledge in psychoanalysis, in Lacan

Para atender às demandas de usuários das novas mídias digitais, experimentações vêm sendo feitas no campo da comunicação midiática. A propagando tem colaborado significativamente nessa busca e usado nas narrativas audiovisuais e o do recurso do storytelling (ou contar histórias). O presente trabalho investiga o uso de narrativas em produtos audiovisuais cuja intencionalidade é transmistir o conteúdo de marca. Tem como objeto dois filmes, que compõem uma campanha publicitária da Panvel Farmácias, hospedados no YouTube e compartilhados pela empresa principalmente no Facebook: os audiovisuais A História do Lilinho (2011) e A História da Sofia (2012). Analisa como a narrativa busca envolver o consumidor emocionalmente para estabelecer um vínculo com a marca a partir do vazio psíquico constitutivo do ser humano. Entende-se que há uma busca de identidade que as histórias solidificam momentaneamente em uma espécie de despropaganda. As redes sociais na internet parecem potencializar essa busca com a possibilidade de interação e produção do que se consome. Uma maneira de explorar a força das narrativas tem sido a adaptação de obras artístico-literárias de modo a atrair e envolver os consumidores. Promoveu-se a análise da narrativa em estudo a partir da intersecção entre Comunicação e Psicologia. Para o estudo do caso recorreu-se a Salmon e Núñez para tratar de storytelling; Kotler para marketing e propaganda; Lévy e Recuero para novas tecnologias e mídias; e Baudrillard e Bauman para sociedade e consumo. Nos campos do audiovisual e da adaptação adotou-se Aumont e Bulhões, bem como Jullier e Marie para auxiliar na análise fílmica. Buscou-se conhecimento também na psicanálise, em Lacan
Audiovisual narratives in social networks: consumption as identity elemento in campaign of Panvel
Keywords: Narrativa (Retorica); Recursos audiovisuais; Mídia digital; Consumo (Economia); Narration (Rhetoric)